2023
DOI: 10.1590/0034-7167-2022-0730
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic profile, diagnoses and nursing care in post-COVID-19 patients in a Brazilian university hospital

Abstract: Objectives: to analyze the sociodemographic profile, diagnoses and nursing care of post-COVID-19 patients admitted to a university hospital in southern Brazil. Methods: a retrospective cohort study. The sample consisted of 1,467 medical records, from January 2020 to January 2021. Results: from the analyzed medical records, the most prevalent profiles, respectively, included: males (52.9%); white (81.1%); with Impaired Physiological Balance Syndrome* Nursing Diagnosis (77.3%); nursing care implementing aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a study conducted by Korhan et al (2014) with intensive care patients, it was determined that the most commonly used nursing diagnosis was Impaired skin integrity, deterioration in oral mucous membrane, and deterioration in verbal communication [21]. In a study conducted by Santos et al (2023) in Brazil, it was determined that the most commonly determined nursing diagnoses in patients were risk for infection, risk for falls, and risk of pressure sores [22]. While the results of the study conducted by Santos et al and In this study, it was observed that the medical hospitalization diagnoses and nursing diagnoses of refugee and native patients hospitalized in the Internal Medicine Clinic were compatible.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Korhan et al (2014) with intensive care patients, it was determined that the most commonly used nursing diagnosis was Impaired skin integrity, deterioration in oral mucous membrane, and deterioration in verbal communication [21]. In a study conducted by Santos et al (2023) in Brazil, it was determined that the most commonly determined nursing diagnoses in patients were risk for infection, risk for falls, and risk of pressure sores [22]. While the results of the study conducted by Santos et al and In this study, it was observed that the medical hospitalization diagnoses and nursing diagnoses of refugee and native patients hospitalized in the Internal Medicine Clinic were compatible.…”
Section: Discussionmentioning
confidence: 99%